Brazil : Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This Selected Issues Paper discusses the macroeconomic implications of pension reforms in Brazil. It assesses empirically the relationship between fiscal policy and the real effective exchange rate in emerging markets and draws policy implications. It reviews the current status of local capital markets in the country, the key challenges, and policy options for further development. The paper also provides a detailed description of consumer credit developments and analyzes recent indicators of household financial distress associated with the credit expansion that has taken place in the last couple of years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet